2021
DOI: 10.1016/j.psj.2020.12.021
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of pulsed ultraviolet light processing for table and hatching eggs

Abstract: In the United States, every year an average of 287.1 eggs are consumed per person, and over 14.1 billion eggs are set in hatchery incubators to produce chicks destined for the egg and meat bird industries. By reducing the microbial load on eggs, food-borne–associated outbreaks can be reduced while good chick health is maintained. Pulsed ultraviolet ( PUV ) light system delivers an energy-intense broad spectrum (100–1,100 nm) pulse derived from a xenon flashlamp. In recent years, PUV ligh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…The temperature, humidity and storage time of the environment during storage are among the effective factors in the formation of these changes. In order to reduce the negative effects of these factors, studies on the effects of processes that do not require heat (Sert et al (2011); Caner and Yüceer (2014); Mehdizadeh et al, 2015;Melo et al 2019;Cassar et al 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The temperature, humidity and storage time of the environment during storage are among the effective factors in the formation of these changes. In order to reduce the negative effects of these factors, studies on the effects of processes that do not require heat (Sert et al (2011); Caner and Yüceer (2014); Mehdizadeh et al, 2015;Melo et al 2019;Cassar et al 2021).…”
Section: Discussionmentioning
confidence: 99%
“…In the researches, various methods were applied after the eggs were collected in order to preserve the quality characteristics of the eggs and to extend the shelf life. Some of these methods are; coating of eggs with various substances (zein (Caner and Yüceer, 2015), soy proteins (Xie et al, 2002), mineral oils (Jirangrad et al, 2010, chitosan (Bhale et al, 2003)) and ultraviolet applications (UV) (Mehdizadeh et al, 2015;Melo et al 2019;Cassar et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Microbes were applied to the surface of eggshells, and the sterilization effect was examined by IPL treatment with different fluences ( Table 3 ). The target microorganisms were E. coli , Salmonella , L. monocytogenes , and Enterococcus faecium ( Cassar et al., 2021a ; Hierro et al, 2009 ; Holck et al, 2018 ; Keklik et al, 2010a ; Lasagabaster et al, 2011 ). Depending on the treatment conditions, E. coli was reduced by 1.6–3.7 Log, Salmonella by 0.7–3.5 Log, and Salmonella enterica by 1.3–7.8 Log ( Hierro et al, 2012 ; Holck et al, 2018 ).…”
Section: Egg Productsmentioning
confidence: 99%
“…Furthermore, it was reported that IPL treatment did not affect the structural or quality characteristics of the cuticle and internal contents of eggshells ( Holck et al., 2018 ; Keklik et al, 2010a ; Lasagabaster et al, 2011 ). In addition, it has been reported that there was no difference between IPL treated egg and untreated egg when they were hatched and grown into chicks ( Cassar et al, 2021a ).…”
Section: Egg Productsmentioning
confidence: 99%
“…Chicken as a type of poultry in the livestock industry is generally divided laying hens and broilers [7], [8]. Companies with a focus on laying hens or broilers can choose or even carry out both cultivation and breeding processes [9], [10]. Badan Pusat Statitik (BPS) noted that the chicken farming industry in Indonesia consists of 397 companies with 20,414 workers with an income of 15.92 trillion.…”
Section: Introductionmentioning
confidence: 99%